PUBLIC LEGAL AWARENESS IN TRAFFIC AS AN APPLICATIVE PRINCIPLE-BASED COMPLIANCE TO PREVENT ACCIDENTS - Vera Novianti; Suci Flambonita; Artha Febriansyah (Sriwijaya Crimen and Legal Studies, 2026)
Public awareness of traffic law is an important factor in the implementation of compliance with the law, a basic principle of a law state. The high number of violations and accidents shows that law enforcement has not fully become a legal culture within society. This study analyzes the role of law enforcement in increasing public legal awareness. The juridical-sociological method is used in this study. This focuses on the clauses in Law Number 22 of 2009 concerning Road Traffic and Transportation, which also examines social factors that influence the level of legal awareness. The result of the study shows that effective law enforcement is not only repressive through sanctions, but also preventive, educative, and persuasive. The public legal awareness forms through the process of internalization law value, which includes knowledge, comprehension, attitude, and a pattern of legal behavior. Therefore, ideal traffic compliance is voluntary and arises from legal awareness, not solely from fear of sanctions. This research emphasizes that synergy between consistent law enforcement, transparency of authorities, and community participation is key in building a culture of traffic order as a manifestation of adherence to principles in community life.